2015 IEEE International WIE Conference on Electrical and Computer Engineering (WIECON-ECE) 2015
DOI: 10.1109/wiecon-ece.2015.7444002
|View full text |Cite
|
Sign up to set email alerts
|

Development of intelligent wheelchair simulator for indoor navigation simulation and analysis

Abstract: Disabilities affect majority of the world population nowadays. Autonomous wheelchair is one of the major assistive systems proposed for the disabled people to meet their daily locomotion challenges. Different algorithm and techniques can be used to find the optimal path in these types of intelligent wheelchair to navigate from a source to destination. Notable change in performance can be observed while testing with different algorithms and techniques. As the real world scenarios are so dynamic, replication of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…To evaluate the indoor navigation system, Testa et al [10], Tao and Ganz [11] proposed a cost-effective simulation framework for all types of users. In the application-wise, Megalingam et al [12] has shown how an intelligent wheelchair was developed and simulated in the virtual environment.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the indoor navigation system, Testa et al [10], Tao and Ganz [11] proposed a cost-effective simulation framework for all types of users. In the application-wise, Megalingam et al [12] has shown how an intelligent wheelchair was developed and simulated in the virtual environment.…”
Section: Introductionmentioning
confidence: 99%